2019
DOI: 10.3389/fimmu.2018.03152
|View full text |Cite
|
Sign up to set email alerts
|

NKG2A Down-Regulation by Dasatinib Enhances Natural Killer Cytotoxicity and Accelerates Effective Treatment Responses in Patients With Chronic Myeloid Leukemia

Abstract: Chronic myeloid leukemia (CML) is a hematological malignancy characterized by the presence of t(9;22) chromosomal translocation that results in BCR-ABL fusion gene. ABL tyrosine kinase inhibitors (TKIs), such as imatinib, nilotinib, and dasatinib, are currently the front-line treatment options for CML. Recently, natural killer (NK) cell activation and expansion have been shown to be associated with optimal treatment responses for CML. To investigate the effects and mechanisms of these TKIs on NK cells, here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…In contrast, an impaired NK cell-mediated cytotoxicity and/or abnormal expression of surface receptors has been observed in patients suffering from leukemia [14][15][16]. Notwithstanding, the studies have been conducted mostly in patients with chronic or myeloid leukemias [17][18][19]. A previous study has reported that peripheral blood NK cells from B-ALL patients have a compromised cytotoxicity towards K562 and autologous blasts.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, an impaired NK cell-mediated cytotoxicity and/or abnormal expression of surface receptors has been observed in patients suffering from leukemia [14][15][16]. Notwithstanding, the studies have been conducted mostly in patients with chronic or myeloid leukemias [17][18][19]. A previous study has reported that peripheral blood NK cells from B-ALL patients have a compromised cytotoxicity towards K562 and autologous blasts.…”
Section: Introductionmentioning
confidence: 99%
“…This led us to hypothesize that dasatinib may be able to promote the development of memory CD8 T-cells (conventional and innate) from the naive-like CD8 T-cell subset in humans. It is also to be noted that numerous studies have found that dasatinib enhances NK cell functions [17][18][19][20][21] . As innate CD8 T-cells share common features with NK cells, we hypothesize that dasatinib could act through the NKG2A or other KIR receptors to enhance the cytotoxicity of innate CD8 T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…This cell expansion is associated with better clinical outcomes in an appreciable proportion of BCR-ABL + CML or acute lymphoblastic leukemia patients 15,16 . Another commonly known fact is the enhancement of NK cell functions under dasatinib treatment [17][18][19][20][21] .…”
mentioning
confidence: 99%
“…The NK/T cells that expanded in response to dasatinib from diagnosis 14 reportedly had antileukemic effects against CML cells, 28‐30 but had not been proven to have antileukemic effects against primitive quiescent CML cells. Sufficient restoration of normal immune effectors that are capable of suppressing primitive quiescent CML cells during DMR may be required for successful TFR.…”
Section: Discussionmentioning
confidence: 99%